2001
DOI: 10.1081/iph-100102566
|View full text |Cite
|
Sign up to set email alerts
|

MODULATORY EFFECT OF CYCLOSPORIN A ONTERT-BUTYL HYDROPEROXIDE–INDUCED OXIDATIVE DAMAGE IN HEPATOCYTES

Abstract: In the present work, we followed an in vitro protective action of cyclosporin A (CsA) against tert-butyl hydroperoxide (t-BHP)-induced oxidative damage in hepatocytes. Various parameters (cell viability, cytosolic calcium level, rhodamine 123 accumulation as indicator of mitochondrial membrane potential and alanine-aminotransferase leakage from cells) were measured as an index of cytotoxicity. Tert-butyl hydroperoxide (1 mM) significantly increased cytosolic Ca2+ and affected mitochondrial membrane potential. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In those articles, we looked for possible underlying common mechanisms of cytoprotection from molecular levels to whole animal studies of various structurally unrelated molecules. We found that several compounds experimentally showed some hepato-ameliorative properties and enumerated possible explanations (Canova et al, 2007;Cerny et al, 2009;Farghali & Masek, 1998;Farghali et al, 1991aFarghali et al, ,b, 1994Farghali et al, , 1996aFarghali et al, ,b, 1997Farghali et al, , 2000bFarghali et al, , 2002Farghali et al, , 2003Gasbarrini et al, 1992aGasbarrini et al, ,b, 1993Kmonickova et al, 2001;Lekic et al, 2011;Sakr et al, 1991a,b).…”
Section: Scientific Rationale For the Traditional Use Of Some Plants mentioning
confidence: 99%
“…In those articles, we looked for possible underlying common mechanisms of cytoprotection from molecular levels to whole animal studies of various structurally unrelated molecules. We found that several compounds experimentally showed some hepato-ameliorative properties and enumerated possible explanations (Canova et al, 2007;Cerny et al, 2009;Farghali & Masek, 1998;Farghali et al, 1991aFarghali et al, ,b, 1994Farghali et al, , 1996aFarghali et al, ,b, 1997Farghali et al, , 2000bFarghali et al, , 2002Farghali et al, , 2003Gasbarrini et al, 1992aGasbarrini et al, ,b, 1993Kmonickova et al, 2001;Lekic et al, 2011;Sakr et al, 1991a,b).…”
Section: Scientific Rationale For the Traditional Use Of Some Plants mentioning
confidence: 99%
“…As a pro‐oxidant, t‐BHP has been used in various studies as a model of oxidative stress . Its many effects on cell metabolism such as changes in calcium homeostasis and increase of lipid peroxidation or decrease of mitochondrial membrane potential have been established. Likewise, the effect of t‐BHP on hypertension and aging has been documented .…”
Section: Introductionmentioning
confidence: 99%
“…As a prooxidant, t-BuOH was widely used in experimental toxicology as a model of liver damage. There is a large body of scientific evidence showing its effects on changes in calcium homeostasis [2], on elevation of lipid peroxidation and decrease of mitochondrial membrane potential [3] [4].…”
Section: Introductionmentioning
confidence: 99%